Flyover’s Contribution in Aggravating the Traffic Problems of Megacities: A Synthesis of Mogbazar-Mouchak Flyover in Dhaka, Bangladesh - Das, Anutosh; Zinia, Faria Afrin; Zubayer, Md Sakib; Salam, Md Abdus; Patwary, A Latif (Journal of Bangladesh Institute of Planners, 2019)
Dhaka, the capital of Bangladesh like most other megacities of the developing countries is regarded as the world’s most broken and paralyzed city due to its dysfunctional transport system. Acute traffic congestion has put the city life into untold sufferings and wasting a large portion of working hour. Considering elevated expressway as a popular means of solving traffic congestion problem, a number of major flyovers have been constructed in Dhaka city and new initiatives are continually going on in this matter. In recent time, it is being observed that the flyovers itself are creating congestion instead of solving it. In this circumstance, this particular research compares the forecasted impact of Mogbazar-Mouchak flyover with the operational experiences after its construction to figure out the factual contribution of flyover in jettisoning lethal traffic congestion problem of Dhaka city. Required primary and secondary data have been collected from a series of field survey and relevant secondary sources. Unfortunately, the multi layered traffic congestion incidents of Mogbazar-Mouchak flyover in at grade and on its ramp from its inauguration, clearly indicates that the very flyover under consideration is tallying more to the ever existed traffic congestion of Dhaka city rather cracking it. Faulty design and shortsighted planning is the reason of increased traffic congestion and the non-functionality of the flyover which deserve close attention to be paid off. This study provides a scope for policymakers to rethink the proposition and role of flyovers in eliminating the transportation problem of megacity Dhaka. JBIP, Vol. 12, 2019 (Printed in June 2020), pp. 63-79